Shear degradation of reinforced concrete beams - Arslan, Guray; Kiristioglu, Izzet (TAYLOR & FRANCIS LTD, 2013)
Reinforced concrete (RC) members are designed to have shear strengths much greater than their flexural strengths to ensure flexural failure according to the current design codes. Flexure failure in beams starts with flexural yielding and shear degradation in the lateral load capacity occurs due to damage related to flexural deformations. Because of the complexity of shear strength degradation, seismic codes tend to be excessively conservative and do not take into account, the contribution of concrete in certain cases. The research described in this paper proves numerical information about the effect of flexure on the shear degradation of RC beams. An analytical equation reflecting the reduction in concrete contribution to shear strength is investigated. It is also observed that the contribution of concrete to shear strength is decreased by an increase the ratio of the shear strength to transverse load capacity calculated from flexural capacity.
Keywords: reinforced concrete; beam; degradation; shear strength; finite element; SEISMIC SHEAR; STRENGTH; COLUMNS; MODEL; DETERIORATION; CAPACITY; Engineering